Land Surface Air Temperature Variations Across the Globe Updated to 2019: The CRUTEM5 Data Set. Issue 2 (20th January 2021) - Osborn, T. J.; Jones, P. D.; Lister, D. H.; Morice, C. P.; Simpson, I. R.; Winn, J. P.; Hogan, E.; Harris, I. C.
Abstract: Climatic Research Unit temperature version 5 (CRUTEM5) is an extensive revision of our land surface air temperature data set. We have expanded the underlying compilation of monthly temperature records from 5, 583 to 10, 639 stations, of which those with sufficient data to be used in the gridded data set has grown from 4, 842 to 7, 983. Many station records have also been extended or replaced by series that have been homogenized by national meteorological and hydrological services. We have improved the identification of potential outliers in these data to better capture outliers during the reference period; to avoid classifying some real regional temperature extremes as outliers; and to reduce trends in outlier counts arising from climatic warming. Due to these updates, the gridded data set shows some regional increases in station density and regional changes in temperature anomalies. Nonetheless, the global‐mean timeseries of land air temperature is only slightly modified compared with previous versions and previous conclusions are not altered. The standard gridding algorithm and comprehensive error model are the same as for the previous version, but we have explored an alternative gridding algorithm that removes the under‐representation of high latitude stations. The alternative gridding increases estimated global‐mean land warming by about 0.1°C over the course of the whole record. The warming from 1861–1900 to the mean of the last 5 years is 1.6°C using the standard gridding (with a 95% confidence interval for errors on individual annual means of −0.11 to +0.10°C in recent years), while the alternative gridding gives a change of 1.7°C. Key Points: We describe the fifth major update of a data set of global land air temperature, CRUTEM5 CRUTEM5 is based on an expanded network of 7, 983 stations (up from 4, 842) and improved identification of outlier values The estimated increase in global land air temperature from 1861–1900 to 2015–2019 is 1.6°C (or 1.7°C with an alternative gridding method)